Artificial fire-works - Jones, Robert (Salt Lake City, UT : Project Gutenberg, 2021)
"Artificial Fire-works: Improved to the Modern Practice" by Robert Jones is a scientific publication written in the mid-18th century. This treatise serves as a comprehensive guide on the art and science of creating various types of fireworks, detailing everything from the essential ingredients and their compositions to the methods of construction. The work aims to provide readers with the necessary knowledge to produce artificial fireworks, thus reducing reliance on foreign artisans for such displays. At the start of the book, the author introduces the topic of fireworks and their rich history, alluding to their origins dating back to ancient civilizations. Jones expresses his intent to offer a detailed, practical guide that covers not only the recipes for various types of fireworks but also specifics on materials like saltpetre, sulphur, and charcoal. He emphasizes clarity and accessibility in his instructions, aiming to educate practitioners in the art of fireworks to improve local expertise in England. The opening sets the stage for an elaborate exploration of not just the ingredients, but also the machinery and techniques essential for crafting mesmerizing displays of light and sound. (This is an automatically generated summary.)
Release date is 2021-01-16
Carol Brown, Chris Curnow and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Fireworks -- Early works to 1800